Systematic review of the role of corticosteroids in cervicofacial infections. Issue 3 (April 2019) - Kent, S.; Hennedige, A.; McDonald, C.; Henry, A.; Dawoud, B.; Kulkarni, R.; Logan, G.; Gilbert, K.; Exely, R.; Basyuni, S.; Kyzas, P.; Morrison, R.; et al.
Abstract: The role of corticosteroids in the management of cervicofacial infections continues to cause controversy. Systemic anti-inflammatory and immunomodulatory effects that reduce swelling and improve symptoms in the head and neck may make these agents an effective addition to the antibiotics used and to surgical management, although this same effect may dull the physiological response to infection, and allow infections to progress. We have systematically reviewed the evidence for the use of corticosteroids in common cervicofacial infections following the PRISMA guidelines. MeSH terms included "head", "neck", "infection", and "glucocorticoid". In total, 31 papers were identified. Eight reported the use of corticosteroids for peritonsillar abscess (PTA), 10 for pharyngitis, four for deep neck space infection (DNSI), four for periorbital cellulitis, and five for supraglottitis. Whilst there is an established evidence base for their use in the treatment of PTA and pharyngitis, other indications need further study, and we highlight the potential pitfalls. The evidence suggests that the use of adjunctive, short-term, high-dose corticosteroids in cervicofacial infections may be safe and effective.